Genomic imbalances and microRNA transcriptional profiles in patients with mycosis fungoides - Garaicoa, Fuad Huaman (2016)
Mycosis fungoides is the most common type of primary cutaneous T cell lymphoma. We have evaluated CDKN2A losses and MYC gains/amplifications by FISH analysis, as well as expression of miR-155 and members of the oncogenic cluster miR-17-92 (miR17, miR18a, miR19b, and miR92a) in MF patients with advanced disease. Formalin-fixed paraffin-embedded skin biopsies from 36 patients at diagnosis, 16 with tumoral MF (T-MF), 13 in histological transformation to a large T cell lymphoma (TR-MF), and 7 cases with folliculotropic variant (F-MF), were studied. Twenty cases showed genomic alterations (GAs): 8 (40 %) had CDKN2A deletion, 7 (35 %) showed MYC gain, and 5 (25 %) exhibited both alterations. GAs were more frequently observed in F-MF (p = 0.004) and TR-MF (p = 0.0001) than T-MF. GAs were significantly higher in cases presenting lesions in head, neck, and lower extremities compared to those observed in trunk and upper extremities (p = 0.03), when ≥25 % neoplastic cells were CD30 positive (p = 0.016) as well as in cases with higher Ki-67 proliferation index (p = 0.003). Patients with GAs showed bad response to treatment (p = 0.02) and short survival (p = 0.04). Furthermore, MF patients showed higher miRNA expression compared to controls (p ≤ 0.0223). T-MF showed higher miR17 and miR-18a expression compared to F-MF and TR-MF (p ≤ 0.0387) while miR19b, miR92a, and miR-155 showed increased levels in F-MF and TR-MF with respect to T-MF (p ≤ 0.0360). Increased expression of miR17 and miR19b in GA group compared to cases without alterations (p ≥ 0.0307) was also detected. Our results add new information about genomic imbalances in MF patients, particularly in F-MF, and extend the present view of miRNA deregulation in this disease.